SAT0030 Circulating Endothelial Microparticles and Endothelial Progenitors Cells in Primary SjÖGren's Syndrome: New Markers of Chronic Endothelial Damage?. (10th June 2014) - Bartoloni, E.; Alunno, A.; Bistoni, O.; Caterbi, S.; Luccioli, F.; Santoboni, G.; Mirabelli, G.; Cannarile, F.; Terenzi, R.; Valentini, V.; Gerli, R.
Abstract : Background: Subclinical atherosclerosis can be considered a form of systemic involvement in patients with chronic inflammatory joint and connective tissue diseases. Multiple factors, including inflammatory and immune-mediated mechanisms, have been identified to promote atherosclerotic endothelial injury [1]. Recent studies focused on role played by the altered balance between endothelial microparticles (EMPs) release and endothelial progenitor cells (EPCs) generation in endothelial wall integrity disruption and subsequent endothelial dysfunction. EPCs represent a new marker of endothelial dysfunction cardiovascular (CV) disease patients and increased EMP levels have been demonstrated in diseases characterized by high inflammatory response, such as polymyalgia rheumatica [2]. There is evidence that primary Sjögren's syndrome (pSS) patients, free of previous CV manifestations, display signs of subclinical atherosclerosis, suggesting a greater CV risk [3, 4]. However, exact pathogenic mechanisms involved in vascular damage in SS are still unclear. Increased levels of leukocyte and platelet MPs, reflecting systemic cell activation, have been demonstrated in SS. On the other hand, the role of EMPs and EPCs in SS has been never investigated. Objectives: To evaluate endothelial injury degree in SS by EMP quantification and their repair potential by EPC and mature EPC measurement and to analyze possible correlation with disease-specific clinical and immunologic features. Methods: 34 female pSS patients and 18 age- and sex-matched normal controls (NC) were enrolled. Number of circulating EMPs (CD31 + /CD42 – ), EPCs (CD34 + /KDR + /CD133 + ) and mature EPCs (CD34 + /KDR + /CD133 – ) was quantified by FACS analysis. Parameters of disease activity and damage were measured by ESSDAI and SSDDI, respectively. Disease-related clinical features, laboratory markers of immunologic dysfunction and traditional CV risk factors were recorded. Results: SS patients displayed higher EMP number with respect to NC (450±155 vs 231±110 n/μl mean ± SD; p<0.0001). Mean concentrations of EPCs as well as mature EPCs resulted significantly higher in patients in comparison to NC (226±181 vs 69±53 n/mL mean ± SD; p<0.001 and 166±161 vs 36±32 n/mL mean ± SD; p<0.0001, respectively). SS patients exhibited a significantly lower EPC/mature EPC ratio in comparison to NC (p<0.01). EMP levels directly correlated with disease duration from symptoms and diagnosis (rho=0.5; p<0.01). EPCs inversely correlated with disease duration from symptoms (rho= -0.5; p<0.01) and diagnosis (rho= -0.4; p<0.05). Conclusions: Present data highlight for the first time a chronic persistent endothelial fragmentation characterizing pSS patients. Endothelial layer reparative potentiality appears to be preserved in the earliest stages of disease. Following disease course, a progressive exhaustion of the precursor endothelial pool may be hypothesized, leading to defective vascular layer restoration and endothelial dysfunction. Further investigations are needed to ascertain the role of EMPs and EPCs in promoting subclinical atherosclerosis in pSS. References: Bartoloni E et al. Arthritis Care Res 2011;63:178 Pirro M et al. J Intern Med 2012;272:177 Vaudo G et al. Arthritis Rheum 2005;52:3890 Gerli R et al. Arthritis Care Res 2010;62:712 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2887